2014
DOI: 10.4315/0362-028x.jfp-13-337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Content and Estimation of Daily Intake of Cadmium and Lead in Several Varieties of Potatoes (Solanum tuberosum L.) Cultivated in the Canary Islands (Spain)

Abstract: Monitoring the metal content in foods such as potatoes is an important aspect of food safety and regulation. Samples of nine varieties of potatoes (73 samples of local potatoes and 77 samples of imported potatoes) were randomly obtained from supermarkets, farmers markets, and farmer plots in Tenerife (Canary Islands, Spain). The edible portion (pulp) was the only part considered for analysis because Spaniards traditionally eat only peeled potatoes. Cadmium (Cd) and lead (Pb) were determined using graphite furn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In order to compare the obtained information, we classified each food item reported according to the Global Individual Information Food Consumption Data Tool (FAO/WHO GIFT) [26], into nine food groups, cereals, roots and tubers, pulses, seeds and nuts, milk, eggs, fish and shellfish, meat, vegetables and fruits, and in their corresponding subgroup; (33), studied other metals (12), without weight base HM´s analysis (57) culinary or plant ingredients (2), fungi studies (33), with sample size ≤1 or without sample size (24), food items with a cooking process or not reported as raw or natural food (3), studies of foods that were identified ≤3 times per food group (1), not identified as edible food (1), all results presented as food group (6), evaluate HM thorough storage containers (5), does not report the country of origin (1) Studies included (n =152)…”
Section: Creation Of Variables For the Food Groups And Subgroupsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare the obtained information, we classified each food item reported according to the Global Individual Information Food Consumption Data Tool (FAO/WHO GIFT) [26], into nine food groups, cereals, roots and tubers, pulses, seeds and nuts, milk, eggs, fish and shellfish, meat, vegetables and fruits, and in their corresponding subgroup; (33), studied other metals (12), without weight base HM´s analysis (57) culinary or plant ingredients (2), fungi studies (33), with sample size ≤1 or without sample size (24), food items with a cooking process or not reported as raw or natural food (3), studies of foods that were identified ≤3 times per food group (1), not identified as edible food (1), all results presented as food group (6), evaluate HM thorough storage containers (5), does not report the country of origin (1) Studies included (n =152)…”
Section: Creation Of Variables For the Food Groups And Subgroupsmentioning
confidence: 99%
“…Then, we considered 359 full-text studies for reading. Of these, 207 were excluded according to the following exclusion criteria: processed food (5), not natural experiment (15), publication before 2011 (2), hunted animals (6), reported animal feed (1), without a measure of central tendency and/or without an exact or precise value of HM (33), studied other metals (12), without weight base HM analysis (57), culinary or plant ingredients (2), fungi studies (33), with sample size ≤ 1 or without sample size (24), food items with a cooking process or not reported as raw or natural food (3), studies of foods that were identified ≤3 times per food group (1), not identified as edible food (1), all results presented as food group (6), evaluated HM thorough storage containers (5), and does not report the country of origin (1). Finally, 152 studies were included (Figure 1).…”
Section: Study Inclusionmentioning
confidence: 99%
See 1 more Smart Citation